Cervical cancer in India and HPV vaccination - Kaarthigeyan, K (Indian Journal of Medical and Paediatric Oncology, 2012)
Cervical cancer, mainly caused by Human Papillomavirus infection, is the leading cancer in Indian women and the second most common cancer in women worldwide. Though there are several methods of prevention of cervical cancer, prevention by vaccination is emerging as the most effective option, with the availability of two vaccines. Several studies have been published examining the vaccine′s efficacy, immunogenicity and safety. Questions and controversy remain regarding mandatory vaccination, need for booster doses and cost-effectiveness, particularly in the Indian context.
Keywords: Cancer; cervix; human papillomavirus; vaccine